Cloning and characterization of a novel functional organic anion transporting polypeptide 3A1 isoform highly expressed in the human brain and testis - Bakos, Éva; Német, Orsolya; Kucsma, Nóra; Tőkési, Natália; Stieger, Bruno; Rushing, Elisabeth; Tőkés, Anna-Mária; Kele, Péter; Tusnády, Gábor E.; Özvegy-Laczka, Csilla (Frontiers in Pharmacology, 2022)
Organic anion transporting polypeptide 3A1 (OATP3A1, encoded by the SLCO3A1 gene) is a prostaglandin, oligopeptide and steroid/thyroid hormone transporter with wide tissue distribution, expressed e.g., in the human brain and testis. Although the physiological importance of OATP3A1 has not yet been clarified, based on its expression pattern, substrate recognition and evolutionary conservation, OATP3A1 is a potential pharmacological target. Previously, two isoforms of OATP3A1, termed as V1 and V2 have been characterized. Here we describe the cloning and functional characterization of a third isoform, OATP3A1_V3. The mRNA of isoform V3 is formed by alternative splicing and results in an OATP3A1 protein with altered C-terminus compared to isoforms V1 and V2. Based on quantitative PCR we demonstrate widespread expression of SLCO3A1_V3 mRNA in human organs, with highest expression in the brain and testis. By generation of an isoform V3-specific antibody and immunostaining, we show that the encoded protein is expressed in the human choroid plexus, neurons, and both germ and Sertoli cells of the testis. Moreover, we demonstrate that, in contrast to isoform V1, OATP3A1_V3 localizes to the apical membrane of polarized MDCKII cells. Using HEK-293 cells engineered to overexpress OATP3A1_V3, we verify the protein’s functionality, and identify dehydroepiadrosterone sulfate as a novel OATP3A1 substrate. Based on their distinct expression pattern but overlapping function, OATP3A1 isoforms may contribute to transcellular (neuro)steroid transport in the central nervous system.